Comparative Assessment of the Human Capital Impact on the Population Income in the European and Asian Regions of Russia - A. A. Aletdinova; A. V. Koritskiy; A. N. Shadrintseva (Статистика и экономика, 2023)
The relevance of the study is explained by the link between economic growth and investment in human capital.The purpose of the study is a comparative analysis of the dynamics of the return of physical and human capital in the European and Asian regions of Russia.Materials and methods. In the article, the authors use the extended Cobb-Douglas production function and conduct a regression spatial analysis based on data of the official Russian statistics.Results. There are estimates of the relationship between the income of the population of regions with the number of employed, with the volume of fixed assets of regions and human capital; the wage fund of the population of regions with the number of employed, with the volume of fixed assets of regions and human capital, the elasticity coefficients are justified. The authors analyzed and interpreted the values of the elasticity coefficients. In particular, the coefficients of elasticity of household income by fixed assets for Asian and European regions tend to decrease; the authors explain this by the low level of investment in the renewal of fixed capital at enterprises. The coefficients of elasticity of income of the population by the number of people employed in the economy of the regions are noticeably higher and tend to increase. At the same time, human capital has a stronger impact on the income of the population than fixed assets and the number of people employed in the economy of the regions. There is a decrease in the influence of human capital on the income of the population in the group of European regions of Russia at the end of the period under review and the relative stability of its returns in the Asian group of regions.Conclusion. The impact of human capital on the income of the population differs significantly in the European and Asian regions of Russia. The authors identified efficiency trends and features of the use of the main factors of production in different groups of regions of the Russian Federation in the period under review. Scientific significance is the generalization of knowledge about the role of human capital in economic development, technology transfer and increasing the investment attractiveness of settlements and regions due to it; obtaining statistically significant models for assessing the economic return of human capital.